The Impacts of an Academic Intervention Based in Metacognition on Academic Performance - Swanson, Holly J.; Ojutiku, Adelola; Dewsbury, Bryan (Teaching and Learning Inquiry, 2024)
Providing reflective opportunities for students to independently develop their metacognition and expand their abilities to make judgments about themselves as learners, including which learning strategies are personally most effective for any given task, have been shown to improve academic performance. We designed a metacognition-based intervention that was structured to provide four weeks of reflective opportunities for students following a metacognitive learning strategies workshop. Qualitative analysis of student responses from the first week’s survey found evidence of metacognitive skill development and self-reported improvements in learning, including an improvement in confidence and preparedness for classes and exams, and better understanding and retention of course content. Our results suggest that students who described an increase in their confidence during the first week were two times more likely to complete the intervention. This completion was correlated with a higher semester GPA, regardless of student identity, prior academic performance, and strategy choice or outcome description during the first week. Read the corresponding ISSOTL blog post here.